Pharmacokinetics, pharmacodynamics, and safety of moss‐aGalactosidase A in patients with Fabry disease. Issue 3 (11th February 2019) - Hennermann, Julia B.; Arash‐Kaps, Laila; Fekete, György; Schaaf, Andreas; Busch, Andreas; Frischmuth, Thomas
Abstract: Moss‐aGalactosidase A (moss‐aGal) is a moss‐derived version of human α‐galactosidase developed for enzyme replacement therapy in patients with Fabry disease. It exhibits a homogenous N‐glycosylation profile with >90% mannose‐terminated glycans. In contrast to mammalian cell produced α‐galactosidase, moss‐aGal does not rely on mannose‐6‐phosphate receptor mediated endocytosis but targets the mannose receptor for tissue uptake. We conducted a phase 1 clinical trial with moss‐aGal in six patients with confirmed diagnosis of Fabry disease during a 28‐day schedule. All patients received a single dose of 0.2 mg/kg moss‐aGal by i.v.‐infusion. Primary endpoints of the trial were safety and pharmacokinetics; secondary endpoints were pharmacodynamics by analyzing urine and plasma Gb3 and lyso‐Gb3 concentrations. In all patients, the administered single dose was well tolerated. No safety issues were observed. Pharmacokinetic data revealed a stable nonlinear profile with a short plasma half‐life of moss‐aGal of 14 minutes. After one single dose of moss‐aGal, urinary Gb3 concentrations decreased up to 23% 7 days and up to 60% 28 days post‐dose. Plasma concentrations of lyso‐Gb3 decreased by 3.8% and of Gb3 by 11% 28 days post‐dose. These data reveal that a single dose of moss‐aGal was safe, well tolerated, and led to a prolonged reduction of Gb3 excretion. As previously shown, moss‐aGal is taken up via the mannose receptor, which is expressed on macrophages but also on endothelial and kidney cells. Thus, these data indicate that moss‐aGal may target kidney cells. After these promising results, phase 2/3 clinical trials are in preparation.